2014
DOI: 10.1134/s1062359014040062
|View full text |Cite
|
Sign up to set email alerts
|

Parental behavior of the beluga whale (Delphinapterus leucas) in natural environment

Abstract: The parental behavior of beluga whales observed in a summer reproductive gathering (near Solovetsky Island, Onega Bay, White Sea) is described, including the parturition process. A tight association between the female and its newborn infant has been traced by the case study of a stillborn calf. Individual behavioral patterns of a mother and calves observable only in natural habitats are detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 16 publications
1
55
1
Order By: Relevance
“…A unique form of mouth-to-mouth social interactions, preliminarily considered a form of play, have been documented between beluga calves (Connor & Peterson, 1994;Dietrich, Garza, Hill, & Aibel, 2013;Krasnova, Chernetsky, Zheludkova, & Bel'kovich, 2014). This form of mouth-tomouth interaction is highly cooperative.…”
Section: Social Playmentioning
confidence: 99%
“…A unique form of mouth-to-mouth social interactions, preliminarily considered a form of play, have been documented between beluga calves (Connor & Peterson, 1994;Dietrich, Garza, Hill, & Aibel, 2013;Krasnova, Chernetsky, Zheludkova, & Bel'kovich, 2014). This form of mouth-tomouth interaction is highly cooperative.…”
Section: Social Playmentioning
confidence: 99%
“…a healthy individual gives attention to an injured or dead one, as summarized in [4]) and is usually seen as a consequence of the cooperative, succouring and protective nature of social mammals [4][5][6][7][8]. Considering that the individual receiving this attention is often an offspring, some authors suggested that this behaviour could be a consequence of the strong mother-offspring bond [9][10][11][12], or a revival attempt through violent manipulation of the bodies [13,14]. In certain cases where the dead or dying individuals were adults, a sexual component and/or a dominance display is involved as observers recorded & 2018 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%
“…Other interactions with non-cetacean marine life, however, are known-or were credibly interpreted by the source authors-to represent play, socio-sexual display, tool-use, feedingrelated behaviour or other functions inconsistent with the hypothesis of surrogates (e.g. Würsig et al, 1989;Smolker et al, 1997;Krützen et al, 2005;Fertl and Fulling, 2007;Martin et al, 2008;Allen et al, 2011Allen et al, , 2017Patterson and Mann, 2011;Araújo and Wang, 2012;Krasnova et al, 2014;Barber, 2016). Finally, several cases of G. macrorhynchus carrying dead sea lions Zalophus californianus (Shane, 1994) or fish-eating O. orca carrying dead salmon (Whitehead et al, 2004) may be fads, confer status or other advantages to the carriers (Shane, 1994;Whitehead et al, 2004;Allen et al, 2017), or possible prey caching.…”
Section: Attentiveness To Non-conspecifics and Inanimate Objectsmentioning
confidence: 99%
“…In such cases, the PA may not be certain that the other individual is dead. An inanimate conspecific can sometimes be revived by forceful manipulation (Krasnova et al, 2014) and the PA may act with the…”
Section: Do Cetaceans Recognise or Comprehend Death?mentioning
confidence: 99%
See 1 more Smart Citation